Optical Fiber Frequency Shift Characterization of Overburden Deformation in Short-Distance Coal Seam Mining - Dingding Zhang; Qiang Chen; Zhengshuai Wang; Jianfeng Yang; Jing Chai (Geofluids)
Overburden deformation is an important concern for the safe and green mining of coal resources. Similarity simulation testing is the main approach used to study the deformation characteristics of the overburden in coal mining. In the application of Brillouin optical time-domain analysis (BOTDA) in similarity simulation tests, the capability of distributed optical fiber sensing (DOFS) to detect the characteristics of the overburden deformation and the evolution is a key factor affecting the testing accuracy. In this study, the relationships between DOFS and overburden deformation and the face impact pressure under geological conditions in short-distance coal seam mining were explored. The results show that DOFS can be used to monitor the strain conditions of the overburden during the entire mining process and can provide the peak positions of the advance support pressure on the face. A DOFS characterization model for investigating the spatial and temporal evolutions of overburden deformation was established. A new method of characterizing the face impact pressure based on the fiber frequency shift variation was developed. The method was demonstrated to be effective through comparison of monitored results of impact pressure counts detected using pressure sensors. The characteristics of the face impact pressure in short-distance coal seam mining were obtained. The results of this study provide valuable guidance for the development of similarity simulation testing and intelligent mining engineering techniques.